Pengaruh Pengalaman Praktik Kerja Industri dan Prestasi Uji Kompetensi Produktif terhadap Kesiapan Memasuki Dunia Kerja Siswa SMK Negeri 1 Malang - Madinatul Munawaroh; Agung Winarno; Sarbini - (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2016)
Abstract : Industrial work practice is one of the vocational high school’s efforts to realize the purposes to produce the high quality of graduate students and readiness to work and also develop the professional attitude which appropriate with students’ major. The purpose of this research is to test: (1) The effect of students’ experience in productive competence test achievement towards students’ readiness to work, (2) The effect of productive competence test achievement towards students’ readiness to work, 3) The effect of students’ experience in industrial work practice and productive competence test achievement towards students’ readiness to work. The type of this research is correlation descriptive. With 108 students as the sample. Multiple regression is used to analyze the data. The result of this research shows that (1) There are positive and significant effects between practical experiences towards students’ readiness to work, (2) There are positive and significant effects between productive competence test achievement towards students’ readiness to work, (3) There are positive and significant effects between students’ experience in industrial work practice and productive competence test achievement towards students’ readiness to work.Abstrak: Praktik Kerja Industri merupakan salah satu upaya untuk merealisasikan tujuan SMK untuk menghasilkan lulusan yang berkualitas dan siap untuk bekerja serta menggambangkan sikap profesional sesuai bidang keahlian masing-masing. Penelitian ini bertujuan untuk menguji: (1) pengaruh pengalaman praktik kerja industri terhadap kesiapan memasuki dunia kerja, (2) pengaruh prestasi uji kompetensi produktif terhadap kesiapan memasuki dunia kerja, (3) pengaruh pengalaman praktik kerja industri dan prestasi uji kompetensi produktif terhadap kesiapan memasuki dunia kerja. Jenis penelitian ini deskriptif korelasi. Dengan sampel 108 siswa kelas XII Program Studi Administrasi Perkantoran di SMKN 1 Malang. Analisis yang digunakan regresi berganda. Hasil penelitian ini menunjukkan; (1) terdapat pengaruh positif dan siginifikan antara pengalaman prakerin terhadap kesiapan memasuki dunia kerja; (2) terdapat pengaruh positif dan signifikan antara prestasi uji kompetensi produktif terhadap kesiapan memasuki dunia kerja; (3) terdapat pengaruh positif dan siginifikan anatara pengalaman praktik kerja industri dan prestasi uji kompetensi produktif terhadap kesiapan memasuki dunia kerja.